Exploring the advances of biosensing technology for the detection of plant pathogens in sustainable agriculture - Shikha, Sneha; Dubey, Saurabh; Kumar, Ranveer; Chandrashekar, Banothu; Namriboi, B. K.; Bhatt, Bhagyashree; Sarkhel, Subhashish; Kashyap, Abhijeet Shankar; Manzar, Nazia; Ghatak, Abhijeet (Frontiers in Bioengineering and Biotechnology, 2026)
Plant pathogens, including fungi, bacteria, viruses, and nematodes, remain major constraints to global agricultural productivity, threatening food security and ecosystem sustainability. Conventional diagnostic methods such as culture-based assays, ELISA, and PCR provide reliable results but are often time-consuming, resource-intensive, and limited in field applicability. Recent advances in biosensing technology have emerged as transformative alternatives, offering rapid, sensitive, and cost-effective detection of plant pathogens. Biosensors (integrating bioreceptors with electrochemical, optical, or piezoelectric transducers) enable real-time monitoring of pathogens at very low concentrations, often before visible symptoms appear. Innovations such as nanomaterial-enhanced platforms, CRISPR-based biosensors, microfluidics, and paper-based devices have improved detection accuracy, portability, and user-friendliness, making them suitable for field deployment. Furthermore, coupling biosensing with digital agriculture tools, artificial intelligence, and IoT facilitates predictive diagnostics, precision crop management, and environmentally sustainable practices. Despite these advances, challenges remain in ensuring long-term stability, affordability, and scalability, particularly for smallholder farmers. Addressing these gaps is essential to achieve widespread adoption. Overall, biosensing technologies hold significant potential to revolutionize plant disease management, minimize yield losses, reduce chemical dependency, and strengthen climate-resilient, sustainable agriculture.